Off-diagonal carrier-phonon coupling and polaron transport - Ye, Jun (2013)
A method extending the Munn-Silbey approach has been applied to obtain the temperature dependence of transport properties of a generalized Holstein model incorporating simultaneous diagonal and off-diagonal carrier-phonon coupling. The Hamiltonian is partially diagonalized by a canonical transformation, and optimal transformation coefficients are determined in a self-consistent manner. Effects of off-diagonal coupling on the optimal transformation coefficients and diffusion coefficients have been discussed in details. The off-diagonal coupling has been revealed as a localization factor as well as a transport mechanism. Moreover, momentum-space variation of the transformation coefficients are found to be responsible for enhanced transport due to off-diagonal coupling.